Current Research in Bilingualism and Bilingual Education (Multilingual Education,, 2018)
This book covers research topics in bilingual education, language policies, language contact, identity of bilingual speakers, early bilingualism, heritage languages, and more, and provides an overview of current theory, research and practice in the field of bilingualism. Each chapter is written by a specialist in the field. Part I focuses on the numerous and heterogeneous relations between languages as well as the implications arising from bilingual speech processing. In Part II, a series of contextualized studies on bilingual classrooms are presented, with diverse research designs applied in different educational settings being a key feature of these studies. Part III bridges theory and practice by offering an insight into mono- and multilingual school settings showcasing examples of educational institutions where bilingualism successfully soared and depicts the needs related to language education.